If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-3)-3=3
We move all terms to the left:
3(x-3)-3-(3)=0
We add all the numbers together, and all the variables
3(x-3)-6=0
We multiply parentheses
3x-9-6=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5
| 10y+1=43 | | -0.03x^2+2.3x-20=0 | | 8x3=8x3= | | 8x3=8x3 | | -44.x=8 | | -40.x=-74 | | 2x+10=-8-7 | | 10m-4=22 | | 0,2=4/x | | 0,2=x/0,4 | | 0,2=0,4/x | | 3(x-3)-2(x-1)=7 | | a÷7=9 | | 5x+4x=32x= | | –7s+9=–6s | | 3x+6-x-1=9 | | xx7=35 | | a)8a+(5a+2)= | | 2x-153x+17=0 | | 3(a+5)=2a-39 | | 25=(14-y) | | 2,5x-9,1=-0,1+2,7x | | 25÷(14-y=) | | 2x+58/8=10 | | 2x+3x+90=360° | | 6x+14/4=10 | | 3x+40/2=2 | | 3x+15/3=10 | | 9=2y-8 | | 8x+56/8=10 | | 40=5x+9) | | 40=5(x+90 |